Genetic and environmental risk structure of internalizing psychopathology in youth. Issue 6 (5th May 2020) - Hettema, John M.; Bourdon, Jessica L.; Sawyers, Chelsea; Verhulst, Brad; Brotman, Melissa A.; Leibenluft, Ellen; Pine, Daniel S.; Roberson‐Nay, Roxann
Abstract: Background: Internalizing disorders (IDs), consisting of syndromes of anxiety and depression, are common, debilitating conditions often beginning early in life. Various trait‐like psychological constructs are associated with IDs. Our prior analysis identified a tripartite model of Fear/Anxiety, Dysphoria, and Positive Affect among symptoms of anxiety and depression and the following constructs in youth: anxiety sensitivity, fearfulness, behavioral activation and inhibition, irritability, neuroticism, and extraversion. The current study sought to elucidate their overarching latent genetic and environmental risk structure. Methods: The sample consisted of 768 juvenile twin subjects ages 9–14 assessed for the nine, abovementioned measures. We compared two multivariate twin models of this broad array of phenotypes. Results: A hypothesis‐driven, common pathway twin model reflecting the tripartite structure of the measures were fit to these data. However, an alternative independent pathway model provided both a better fit and more nuanced insights into their underlying genetic and environmental risk factors. Conclusions: Our findings suggest a complex latent genetic and environmental structure to ID phenotypes in youth. This structure, which incorporates both clinical symptoms and various psychological traits, informs future phenotypic approaches for identifying specific genetic and pathophysiological mechanisms underlying ID risk.